Around the plastic world in 455 days - a citizen science global transect quantifying microplastics in the oceans - Scarlett, Alan; Lintern, Gina M; Copeland, Aaron D; Sanders, Jon; Davis, Stephen; Grice, Kliti (Western Australian Organic & Isotope Geochemistry Centre, 2022)
Public perception of plastics in the oceans has increased over the last few decades, but only more recently has the potential harm to organisms due to ingestion of microplastics started to be recognized. The monitoring of larger plastics lends itself to Citizen Science projects but sample collection and analysis of microplastics (0.05 – 5 mm) is more challenging. In this Citizen Science project, world-renowned, single-handed yachtsman Jon Sanders (AO, OBE) teamed up with Western Australian Isotope and Geochemistry Centre (WA-OIGC) researchers at Curtin University, to raise awareness of microplastics in the oceans, and to quantify the numbers of microplastic particles present along a global transect using daily water filtration. In particular, the study aimed to provide data for remote areas of the southern hemisphere for which very little data existed previously. The voyage was carried out by Jon Sanders on board Yacht Perie Banou II, departing Fremantle port, Western Australia, on 3rd November 2019 and returning on 31st January 2021, a total of 455 days (somewhat longer than anticipated due to the Covid-19 Pandemic) and spanning 46,100 km. Approximately 115 L of seawater was pumped per day from an inlet in the hull, close to the bow of Perie Banou II, and filtered onto stainless steel woven filters with 43 µm aperture (equivalent imperial: mesh 325). No plastic was present in the filtration system. During stopovers in ports, the filters were couriered to the WA-OIGC laboratories for processing and analyzes by Attenuated Total Reflectance (ATR) Fourier-transform infrared spectroscopy (FTIR). A total of 177 filters were analyzed resulting in a mean count of 33 microplastics m-3 seawater across the entire global transect. The Pacific Ocean was found to contain the least numbers of microplastic particles with 23 and 15 microplastics m-3 seawater for the eastern and western sides of the Pacific transect respectively. The highest recorded numbers were 291 and 246 microplastics m-3 seawater for two contiguous stations south of the equator in the Atlantic Ocean, both of which were over 600 km from the Brazilian coastline. Microplastic particles found were typically close to the lower size limit defined as microplastic i.e. 50 µm and were mostly grey/black in color. The collaboration between Jon Sanders’ Citizen Science team and WA-OIGC researchers was highly successful. The study was the first global transect of microplastics in the oceans that utilized consistent sampling methods throughout. The data was consistent with other scientific surveys of remote areas of ocean and could act as a benchmark for future studies into microplastics in the oceans.